2017
DOI: 10.1016/j.neuroscience.2017.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Microglia density decreases in the rat rostral nucleus of the solitary tract across development and increases in an age-dependent manner following denervation

Abstract: Microglia are critical for developmental pruning and immune response to injury, and are implicated in facilitating neural plasticity. The rodent gustatory system is highly plastic, particularly during development, and outcomes following nerve injury are more severe in developing animals. The mechanisms underlying developmental plasticity in the taste system are largely unknown, making microglia an attractive candidate. To better elucidate microglia’s role in the taste system, we examined these cells in the ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 78 publications
7
19
0
Order By: Relevance
“…In contrast, microglial proliferation and density increases in the VTA are more gradual and the magnitude of microglial overproduction is less pronounced. Microglial overproduction in the NAc also appears to exceed that reported for microglia in other regions such as the brainstem (Riquier & Sollars, 2017) and cortex (Askew et al, 2017;Hagemeyer et al, 2017) and be comparable to that observed in hippocampus (Kim et al, 2015). Cerebellum is the only region where reported microglial overproduction exceeds the levels we find in the NAc (Hagemeyer et al, 2017).…”
Section: Regional Differences In the Developmental Maturation Of MIsupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, microglial proliferation and density increases in the VTA are more gradual and the magnitude of microglial overproduction is less pronounced. Microglial overproduction in the NAc also appears to exceed that reported for microglia in other regions such as the brainstem (Riquier & Sollars, 2017) and cortex (Askew et al, 2017;Hagemeyer et al, 2017) and be comparable to that observed in hippocampus (Kim et al, 2015). Cerebellum is the only region where reported microglial overproduction exceeds the levels we find in the NAc (Hagemeyer et al, 2017).…”
Section: Regional Differences In the Developmental Maturation Of MIsupporting
confidence: 67%
“…In the adult CNS, long-term in vivo imaging and clonal analysis have shown that microglia proliferate and undergo cell death to maintain consistent numbers (Askew et al, 2017;Füger et al, 2017;Réu et al, 2017;Tay, Savage, Hui, Bisht, & Tremblay, 2017). Reports from several brain regions have also shown that microglial density increases during early postnatal development but then declines by adulthood (Askew et al, 2017;Hagemeyer et al, 2017;Kim et al, 2015;Riquier & Sollars, 2017). However, whether this decrease in microglial abundance was due to tissue growth or other mechanisms was not investigated.…”
Section: Microglia Undergo Developmental Overproduction and Refinemmentioning
confidence: 99%
“…Microglial density measured in control pups was comparable to values reported in studies investigating the rostral region of the rat NTS at a similar age (Riquier & Sollars, ). However, the lack of sex‐based differences in density or morphological features contrasts with previous observations in the cortex, hippocampus, paraventricular nucleus and amygdala of rats, where males began to show increased microglial numbers compared with females after perinatal testicular androgen secretion (Schwarz, Sholar, & Bilbo, ).…”
Section: Discussionsupporting
confidence: 83%
“…An increase in microglial density has also been reported in the hippocampus of P14 mice pups after a similar NMS protocol (Delpech et al., ); however, magnitude of the effect reported in Figure of the present study was more modest. During development, microglial density in the rostral NTS of rats peaks near P14, and a ‘ceiling effect’ has been suggested to explain the small increase in density after transection of the chorda tympani nerve (Riquier & Sollars, ). Although the rostral and caudal regions of the NTS are functionally distinct, there might be a similar explanation for the limited effects of NMS in the medulla.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were perfused and both the right and left GG were extracted between 567 and 937 (M = 643) days after surgery. Central immune responses in neonatal rats do not differ between the NTS contralateral to CTX and the NTS of unoperated or Sham-sectioned control rats (Riquier & Sollars, 2017). Therefore, neurons in the GG contralateral to CTX are unlikely to be damaged, making the contralateral GG an appropriate control.…”
Section: Geniculate Ganglionmentioning
confidence: 94%